Perhitungan Konstruksi Bangunan Atas pada Modifikasi Barge 345 Feet Menjadi Accomodation Work Barge - Widodo, Panut; Suyanto, Suyanto (Universitas Ivet, 2025)
The need for ship units can be met by building new ships, purchasing second ships that are still viable, chartering ships, and modification of existing ships. Decision considerations may include ship building time, level of urgency or budget. One of the decisions a ship owner can take considering budget, time and owned existing ship is by modifying the ship according to their needs, for example modification of a flat top barge (FTB) to an accommodation work barge (AWB). The need for plate material, especially when modifying FTB to AWB, requires construction calculations for the modified part. The modification made was to create accommodation space above the main deck. The accommodation space construction calculations are adjusted rules BKI 2022 about classification and construction, part I, volume II. From data of general arrangement and BKI rules, the results show that thickness of plate outer wall of superstructure and boat deck is 8 mm, thickness of room bulkhead plate, navigation deck and top deck is 6 mm, size of the internal construction in accommodation room/boat deck is frame/stiffener/deck beam profile L90+90 x 8 mm, web frame/web stiffener/strong beam profile L120+120 x 10 mm, deck girder profile T150+80 x 8 mm.